mọi người giúp em cậu này với ạ nhanh
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1 The meeting was canceled 3 days ago
2 She told me she was watching a film with her sister then
3 I admire the guitarist who is perfroming on the stage
4 Had it not been for Pauline's interest, the project would have been abandoned
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Đề dài thế này sao giải thích nhanh cho e đc
Part 1
1 C
2 B
3 D
4 C
5 B
6 A
Part 2
1 T
2 F
3 F
4 F
V
1 That old house has just been bought
2 If he doesn't take these pills, he won't be better
3 I suggest taking a train
4 Spending the weekend in the countryside is very wonderful
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 10:
a: ĐKXĐ: \(\left\{{}\begin{matrix}x\notin\left\{2;-1\right\}\\y\ne-5\end{matrix}\right.\)
\(A=\dfrac{y+5}{x^2-4x+4}\cdot\dfrac{x^2-4}{x+1}\cdot\dfrac{x-2}{y+5}\)
\(=\dfrac{y+5}{y+5}\cdot\dfrac{\left(x^2-4\right)}{x^2-4x+4}\cdot\dfrac{x-2}{x+1}\)
\(=\dfrac{\left(x^2-4\right)\cdot\left(x-2\right)}{\left(x+1\right)\left(x^2-4x+4\right)}\)
\(=\dfrac{\left(x+2\right)\left(x-2\right)\cdot\left(x-2\right)}{\left(x+1\right)\left(x-2\right)^2}=\dfrac{x+2}{x+1}\)
b: \(A=\dfrac{x+2}{x+1}\)
=>A không phụ thuộc vào biến y
Khi x=1/2 thì \(A=\left(\dfrac{1}{2}+2\right):\left(\dfrac{1}{2}+1\right)=\dfrac{5}{2}:\dfrac{3}{2}=\dfrac{5}{2}\cdot\dfrac{2}{3}=\dfrac{5}{3}\)
Câu 12:
a: \(A=\dfrac{x}{x+3}+\dfrac{2x}{x-3}+\dfrac{9-3x^2}{x^2-9}\)
\(=\dfrac{x}{x+3}+\dfrac{2x}{x-3}+\dfrac{9-3x^2}{\left(x+3\right)\left(x-3\right)}\)
\(=\dfrac{x\left(x-3\right)+2x\left(x+3\right)+9-3x^2}{\left(x+3\right)\left(x-3\right)}\)
\(=\dfrac{x^2-3x+2x^2+6x+9-3x^2}{\left(x+3\right)\left(x-3\right)}\)
\(=\dfrac{3x+9}{\left(x+3\right)\left(x-3\right)}=\dfrac{3\left(x+3\right)}{\left(x+3\right)\left(x-3\right)}=\dfrac{3}{x-3}\)
b: Khi x=1 thì \(A=\dfrac{3}{1-3}=\dfrac{3}{-2}=-\dfrac{3}{2}\)
\(x+\dfrac{1}{3}=\dfrac{10}{3}\)
=>\(x=\dfrac{10}{3}-\dfrac{1}{3}\)
=>\(x=\dfrac{9}{3}=3\left(loại\right)\)
Vậy: Khi x=3 thì A không có giá trị
c: \(B=A\cdot\dfrac{x-3}{x^2-4x+5}\)
\(=\dfrac{3}{x-3}\cdot\dfrac{x-3}{x^2-4x+5}\)
\(=\dfrac{3}{x^2-4x+5}\)
\(x^2-4x+5=x^2-4x+4+1=\left(x-2\right)^2+1>=1\forall x\) thỏa mãn ĐKXĐ
=>\(B=\dfrac{3}{x^2-4x+5}< =\dfrac{3}{1}=3\forall x\) thỏa mãn ĐKXĐ
Dấu '=' xảy ra khi x-2=0
=>x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
1. English is more interesting than music.
2. Today they are not as happy as they were yesterday.
3. Ha Noi is not as small as Hai Duong.
4. Mai's sister is not as pretty as her.
6. You have got more money than me.
7. Art is not as difficult as French.
8. Nam's father is more careful than him.
9. No one in our town is as rich as Mr Ron.
10. He is the most intelligent in my class.
11. Everest is the highest mountain in the world.
12. Minh is the fattest person in my group.
13. I can't swim as far as Jan.
14B 15C 16A 17C 18B 19C 20B
![](https://rs.olm.vn/images/avt/0.png?1311)
Chiều rộng mảnh đất hình chữ nhật đó là:7,8+6,4=14,2(m)
Chu vi mảnh đất hình chữ nhật đó là:(7,8+14,2)×2=44(m)
Diện tích mảnh đất hình chữ nhật đó là:7,8×14,2=110,76(m²)
Đáp số:Chu vi:44m
Diện tích:110,76 m²
Chúc học tốt!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
Đề 1:
Bài 1:
\(a,=\sqrt{\left(\sqrt{7}+1\right)^2}-\left|-1+\sqrt{7}\right|=\sqrt{7}+1-\sqrt{7}+1=2\\ b,=2\sqrt{2}-4\sqrt{2}-5\sqrt{2}+\dfrac{\sqrt{2}}{2}=\dfrac{\sqrt{2}}{2}-7\sqrt{2}=\dfrac{-13\sqrt{2}}{\sqrt{2}}\)
Bài 2:
\(PT\Leftrightarrow\sqrt{\left(x-\dfrac{1}{2}\right)^2}=\dfrac{1}{2}\Leftrightarrow\left|x-\dfrac{1}{2}\right|=\dfrac{1}{2}\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{2}+\dfrac{1}{2}=1\\x=-\dfrac{1}{2}+\dfrac{1}{2}=0\end{matrix}\right.\)
Bài 3:
\(a,M=\dfrac{a-2\sqrt{a}+1}{\sqrt{a}\left(\sqrt{a}-1\right)}\cdot\dfrac{2\sqrt{a}}{\left(\sqrt{a}-1\right)\left(\sqrt{a}+1\right)}=\dfrac{2\left(\sqrt{a}-1\right)^2}{\left(\sqrt{a}-1\right)^2\left(\sqrt{a}+1\right)}=\dfrac{2}{\sqrt{a}+1}\\ b,M< 1\Leftrightarrow\dfrac{2}{\sqrt{a}+1}-1< 0\Leftrightarrow\dfrac{1-\sqrt{a}}{\sqrt{a}+1}< 0\\ \Leftrightarrow1-\sqrt{a}< 0\left(\sqrt{a}+1>0\right)\\ \Leftrightarrow a>1\)